Physicochemical and mechanical properties of selected cohesive soils of Lublin region used in waterproofing applications - Gazda, Lucjan; Franus, Małgorzata (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
In this paper preliminary characteristics of selected cohesive soils of Lublin region that can be used in waterproofing applications in geotechnics and constructions is presented. The investigations and analysis were made according to the applicability criteria of materials used as mineral waterproofing barriers which have been elaborated in the last years in Institute of Building Techniques. On the basis of petrographical, mineral, filtering, structural and mechanical properties, the usability of slits from Bychawa and Łążek Ordynacki and powdery clay from Markowicze was confirmed, whereas glauconitic clay from Gawłówka did not meet all the criteria. The study has shown that a great number of parameters that determine the usability criteria, are resulting from petrography and mineralogy of the soils. A perfect suitable soil for that purpose has not been found, but a complementation of parameters in particular types of soils has been detected. This result gives a possibility to obtain composite materials (multilayered and homogenized).